State stabilization macroeconomic policy: features and prospects for Ukraine - Roman Kalinovskyi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The research reveals the essence of the process of state stabilization macroeconomic policy, which includes two main directions: fiscal policy influence on the budget balancing and monetary regulation of economy through the transmission mechanism improvement and monetary regime defining. The key problems connected with the state budget deficit are investigated. The state and dynamics of the Ukraine state budget are considered. The ways of overcoming the consequences of state budget imbalances are analyzed. The concept of transmission mechanism was defined. Were shown and explained all the key channels of monetary transmission used in Ukraine and in the world, and were suggested the ways to improve their efficiency, which in future may lead to the improvement of the economic situation in Ukraine. Was justified the necessity of improving the transmission mechanism for the monetary policy strategic objectives achieving. Were given the recommendations on how to improve the channels of transmission mechanism in Ukraine with the aim of increasing the effectiveness of monetary stabilization policy. The basic monetary regimes implementation in various countries of the world and the resulting consequences are researched. The benefits of inflation targeting regime for the state’s monetary policy effectiveness enhancing are justified. Recommendations for further implementation of the inflation targeting regime in Ukraine are provided.